Design and implementation of 3D graphics systems - Gomes, Jonas; Velho, Luiz; Costa Sousa, Mario 1967- (CRC Press, 2013)
"Design and Implementation of 3D Graphics Systems covers the computational aspects of geometric modeling and rendering 3D scenes. Special emphasis is given to the architectural aspects of interactive graphics, geometric modeling, rendering techniques, the graphics pipeline, and the architecture of 3D graphics systems. The text describes basic 3D computer graphics algorithms and their implementation in the C language. The material is complemented by library routines for constructing graphics systems, which are available for download from the book's website. This book, along with its companion Computer Graphics: Theory and Practice, gives readers a full understanding of the principles and practices of implementing 3D graphics systems."